New Landscapes. (New York : The Gallery, Three Zero, 1992)
Abrams, Michael ; Anthony, Carol ; Bery, Robert ; Bierk, David ; Blondes, Jeffrey ; Chambers, McWillie ; Gray, Larry ; Gregory, Michael ; Hambleton, Susan
New Landscapes, The Gallery, Three Zero, New York, 1992
boek